Development of the Pot Artistry Game to Stimulate Fine Motor Skills in Children Aged 5-6 Years - Al-Haq, Opie Faradika Avilian Imani; Pramono, Pramono; Tirtaningsih, Munaisra Tri; Putra, Yudithia Dian (Proceedings Series of Educational Studies, 2024)
This research aims to develop an educational toy to stimulate fine motor skills in children aged 5-6 years, responding to the lack of such tools in several educational institutions. Referring to the Regulation of the Minister of Education & Culture Number 137 of 2014 on National Standards for Early Childhood Education, specifically the Fine Motor Indicators for ages 5-6 years, researchers designed the "Pot Artistry" game. The research methodology adopts a synthesis by Pramono et al. (2019), combining approaches from several previous researchers. The development process comprises six stages, from needs analysis to small group testing. Validation was conducted by two game experts and two fine motor skills experts, with trials involving 20 kindergarten B children at TK Baitul Makmur, Dau, Malang Regency. The game expert validation results reached 87.5% (highly valid), while the material expert validation achieved 97.2% (highly valid). Observations on children showed a score of 88% for aspects of interest and mot